Nutrition, body composition, and performance: a case study of two collegiate wrestlers: case study - Coapstick, G.-J.; Barry, A. M.; Shoemaker, M. E. (Journal of Exercise and Nutrition, 2024)
Introduction: This case-study examined changes in nutrient intake, body composition, and performance of two Division I wrestlers before and after competition season.